Canine retraction and anchorage loss Self-ligating versus conventional brackets in a randomized split-mouth study - Monini, Andre da Costa [UNESP]; Gandini Júnior, Luiz Gonzaga [UNESP]; Martins, Renato Parsekian [UNESP]; Vianna, Alexandre Protasio [UNESP] (E H Angle Education Research Foundation, Inc, 2014)
Objective: To evaluate the velocity of canine retraction, anchorage loss and changes on canine and first molar inclinations using self-ligating and conventional brackets.Materials and Methods: Twenty-five adults with Class I malocclusion and a treatment plan involving extractions of four first premolars were selected for this randomized split-mouth control trial. Patients had either conventional or self-ligating brackets bonded to maxillary canines randomly. Retraction was accomplished using 100-g nickel-titanium closed coil springs, which were reactivated every 4 weeks. Oblique radiographs were taken before and after canine retraction was completed, and the cephalograms were superimposed on stable structures of the maxilla. Cephalometric points were digitized twice by a blinded operator for error control, and the following landmarks were collected: canine cusp and apex horizontal changes, molar cusp and apex horizontal changes, and angulation changes in canines and molars. The blinded data, which were normally distributed, were analyzed through paired t-tests for group differences.Results: No differences were found between the two groups for all variables tested.Conclusions: Both brackets showed the same velocity of canine retraction and loss of anteroposterior anchorage of the molars. No changes were found between brackets regarding the inclination of canines and first molars.
Keywords: Canine retraction; Anchorage; Self-ligating brackets; Tooth movement rate